Physician assisted-dying in mentally and somatically ill individuals in Switzerland: Protocol for survey-based study - Kowalinski, Eva; Ziltener, Tiziana; Staub, Sarah; Moeller, Julian; Trachsel, Manuel; Schneeberger, Andres R.; Franke, Irina; Lang, Undine E.; Huber, Christian G. (Frontiers in Psychiatry, 2022)
Background Article 115 of the Swiss Penal Code (StGB) permits physician-assisted dying (PAD), provided it is not performed for “selfish reasons,” and thus, occupies a special role in international comparison. However, the Swiss federal law does not regulate who exactly is entitled to access PAD, and there is no universal agreement in the concerned professional societies. Additional uncertainty arises when assessing the wish for PAD of a mentally ill person compared to a somatically ill person. Objectives This study aims to contribute to the discussion of PAD among the mentally ill and to provide insight into the current situation in Switzerland. Methods This is a monocentric prospective observational survey-based study. We will conduct an exploratory online/telephone survey about PAD in somatic vs. mental illness in Switzerland. The survey sample will comprise 10,000 Swiss residents of the general population from all three language regions (German, Italian, and French) as well as 10,000 medical professionals working in the seven states (“cantons”) of Basel-Stadt, Basel-Landschaft, Aargau, Lucerne, Graubünden, Ticino, and Vaud. Opinions on PAD in mentally and somatically ill patients will be assessed using 48 different case vignettes. Each participant will be randomly assigned a somatic terminal, a somatic non-terminal, and a mental non-terminal case vignette. Furthermore, the attitude toward the ethical guidelines of the Swiss Medical Association of 2004, 2018, and 2022, as well as the stigmatization of mentally ill people will be assessed. Discussion Physician-assisted dying in mentally ill persons is a highly relevant yet controversial topic. On the one hand, mentally ill persons must not be discriminated against in their desire for PAD compared to somatically ill persons while at the same time, their vulnerability must be considered. On the other hand, treating physicians must be protected in their ethical integrity and need security when judging PAD requests. Despite its relevance, data on PAD in the mentally ill is sparse. To regulate PAD for the mentally ill, it is therefore important for Switzerland—but also internationally—to gain more insight into the ongoing debate. Clinical trial registration ClinicalTrials.gov, identifier: NCT 05492461.